Lembaga Pendidikan Sekolah dan Madrasah - A, Arifuddin; Rama, Bahaking; S, Syamsuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the era of increasingly widespread globalization, every nation needs to increase its competitiveness in various fields, especially its human resources. In order to be able to compete, everyone is required to be able to develop science and technology. In order to answer the increasingly difficult challenges, educational institutions must make significant changes, in order to produce human resources who are able to respond to every change. Many things are problems and challenges in the world of education, including madrasas. All the challenges and problems faced require serious solutions, in order to produce quality human resources in terms of science, technology and good morals. In this case, madrasas as one of the Islamic educational institutions in order to meet these demands strive to make changes and developments continuously in order to produce quality graduates. This study is a literature review with a qualitative approach. The results of the study show that the educational system renewal model offered includes the contents of the curriculum and learning methods. The curriculum offered uses a combination model while still teaching Islamic lessons plus general subjects, such as reading and writing Latin letters, arithmetic, language, natural sciences, social sciences and several types of skills. While the method used applies modern learning methods to be more effective.